عزالدین بن عبدالسلام کا تصورِ بدعت: ایک مطالعہ (Al-Qamar, 2020)
The induction of self-made new ideas and deeds into the religion is called "Bidʻah" or innovation in Islamic circles.  It has been the subject of great debate among Muslim scholars. This paper studies the theory of Bidʻah introduced by ʻIzz al-Dīn IbnʻAbd al-Salām (1180-1262), a Shāfʻī theologian and Jurist. It concludes that the difference of opinion among the scholars on the division of Bidʻah is based on the definition of the word. The division of Bidʻah is based on its literal meaning. No scholar is convinced that Sharʻī Bidʻah is virtuous. Based on the literal meaning of the word, it is not wrong to divide the Sharʻī Bidʻah into five categories. Despite calling Bidʻah Ḥasanah, by ʻIzz al-Dīn has rejected some of the innovative creeds and deeds which seemed to be very virtuous. So it is not fair to make ʻIzz al-Dīn’s mentioned view an argument for any self-made action or Bidʻah.
Keywords: ʻIzz al-Dīn IbnʻAbd al-Salām; Bidiʻah